2021
DOI: 10.1038/s41467-021-21975-x
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning method for HLA imputation and trans-ethnic MHC fine-mapping of type 1 diabetes

Abstract: Conventional human leukocyte antigen (HLA) imputation methods drop their performance for infrequent alleles, which is one of the factors that reduce the reliability of trans-ethnic major histocompatibility complex (MHC) fine-mapping due to inter-ethnic heterogeneity in allele frequency spectra. We develop DEEP*HLA, a deep learning method for imputing HLA genotypes. Through validation using the Japanese and European HLA reference panels (n = 1,118 and 5,122), DEEP*HLA achieves the highest accuracies with signif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 63 publications
2
54
0
Order By: Relevance
“…Given the growing diversity of HLA alleles, deep learning could help increase the number of alleles that could be imputed accurately when more data is available [34]. Recently, Naito et al independently published an effective multitask CNN architecture for HLA imputation that is very similar to the one proposed in this work [26]. This work confirms the effectiveness of this deep learning approach, and provides an additional occlusion analysis.…”
Section: Introductionsupporting
confidence: 67%
“…Given the growing diversity of HLA alleles, deep learning could help increase the number of alleles that could be imputed accurately when more data is available [34]. Recently, Naito et al independently published an effective multitask CNN architecture for HLA imputation that is very similar to the one proposed in this work [26]. This work confirms the effectiveness of this deep learning approach, and provides an additional occlusion analysis.…”
Section: Introductionsupporting
confidence: 67%
“…Given their critical impact on immune responses and contribution to host genetics of various infectious diseases, 26,27 HLA gene variants have been investigated for their possible role in the response to COVID-19 infection with controversial discussions 28,29 . To address this issue, we applied in silico imputation of both classical and non-classical HLA variants using the HLA reference panel of Japanese ( n = 1,118) 30,31 . After imputing the HLA variants, we did not observe association signals satisfying neither of the genome-wide significance ( P < 5.0 × 10 -8 ) or HLA-wide significance thresholds ( P < 0.05/2,482 variants = 2.0 × 10 -5 ; Supplementary Figure 3 and Supplementary Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…HLA genotype imputation was performed using DEEP*HLA software (version 1.0), a multitask convolutional deep learning method 31 . We used the population-specific imputation reference panel of Japanese ( n = 1,118), which included both classical and non-classical HLA gene variants for imputation 30 .…”
Section: Methodsmentioning
confidence: 99%
“… 20 Furthermore, MHC fine‐mapping for a trans‐ethnic cohort can boost its power of revealing genetic features that affect complex diseases beyond ethnicities by removing confounding by linkage. 21 , 22 We performed trans‐ethnic MHC fine‐mapping of PD using GWAS data in European and East Asian populations and identified that specific amino acid positions of HLA‐DRβ1 and HLA‐B were independently associated with PD risk across ethnicities. Furthermore, the risk‐associated alleles of HLA‐DRB1 presented variable binding affinity to a known α‐synuclein epitope in in silico prediction, suggesting their functional role to the pathogenesis of PD.…”
mentioning
confidence: 99%